Cellular neural networks and their applications - Stoynov, Pavel (AIP conference proceedings, 2019)
The article presents the Cellular Neural Networks (CNN), their architectures and classifications. As a natural tool for approximation of Partial Differential Equations (PDE), CNN offer numerous applications for modeling phenomena in nature and society. Some of these applications are considered in the article.